Registration of 'CP 06‐2425', 'CP 06‐2495', 'CP 06‐2964', 'CP 06‐3103', and 'CP 07‐1313' Sugarcane for Sand Soils in Florida. Issue 2 (27th April 2017) - Singh, Maninder P.; Comstock, Jack C.; Davidson, Wayne; Gordon, Vanessa; Sandhu, Hardev S.; McCord, Per; Zhao, Duli; Sood, Sushma; Baltazar, Miguel; McCorkle, Katherine
Abstract : 'CP 06‐2425' (Reg. No. CV‐172, PI 678574), 'CP 06‐2495' (Reg. No. CV‐173, PI 678575), 'CP 06‐2964' (Reg. No. CV‐174, PI 678576), 'CP 06‐3103' (Reg. No. CV‐175, PI 678577), and 'CP 07‐1313' (Reg. No. CV‐176, PI 678578) sugarcane (a complex hybrid of Saccharum spp.) were released in June 2015 to be cultivated on mineral (sand) soils in Florida. These five sugarcane cultivars were developed through cooperative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugarcane League, Inc. Female and male parents are: CP 01‐1625 and 03 P 29 for CP 06‐2425; CP 94‐2095 and CP 97‐1387 for CP 06‐2964; 'TCP 00‐4519' and 'CP 84‐1198' for CP 07‐1313; and unknown for both CP 06‐2495 and CP 06‐3103. Averaged across three crop cycles, CP 06‐2425, CP 06‐2495, CP 06‐2964, CP 06‐3103, and CP 07‐1313 had 22.4, 32.7, 18.0, 23.4, and 23.7% higher cane yield than 'CL 88‐4730', a commercial reference cultivar. These cultivars were released by the Florida Sugarcane Variety Committee due to their high cane and sucrose yields particularly in the ratoon crops and acceptable levels of resistance to brown rust, orange rust except for CP 06‐2425, smut, leaf scald, Sugarcane mosaic virus strain E (mosaic), and ratoon stunt.